2014
DOI: 10.1177/0886109913519792
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Domestic Violence Protection Law by Vietnamese Immigrant Wives in Taiwan

Abstract: This article explores the structural factors that hinder Vietnamese immigrant wives from escaping domestic violence by applying an institutional ethnography perspective. Taiwan’s Domestic Violence Prevention Law requires the government to assign professionals to help abused victims, but the law in action shows that abused Vietnamese wives must go through multiple institutions, which put different structural constraints on them, to reach the goal of escaping domestic violence. Following the structural intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Respondents from other ethnic groups also noted police discrimination. In Tang and Wang’s (2014, p. 280) study, a social worker reported that the police ‘were not neutral and deliberately provided incorrect information…’ to immigrant Vietnamese victims in Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…Respondents from other ethnic groups also noted police discrimination. In Tang and Wang’s (2014, p. 280) study, a social worker reported that the police ‘were not neutral and deliberately provided incorrect information…’ to immigrant Vietnamese victims in Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also opined that most of these cross-border wives entered these arrangements illegally, some trough trafficking, prostitution, matchmaking, or some sorts of arrangements, which soon affects their status making them vulnerable to domestic violence as a postmigration effect (Chiu & Choi, 2020;Choi & Cheung, 2017;Deniz & Özgür, 2021). RQ2 found risk factors as the characteristic of domestic violence on these women and RQ 3 (Tschirhart, Straiton et al, 2019) *** ** ** 7/Good (Tschirhart, Diaz et al, 2019) *** * ** 7/Good (Anitha, Yalamarty et al, 2018) & 4 are the effects of domestic violence on cross-border wives and coping strategies adopted by victims (Tang & Wang, 2014;Williams, 2010a;Williams & yu, 2006) (Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…Studies also described other immigration policies and restrictions on citizenship rights such as right to residency status by country, Taiwan imposed 3 years of immigration restriction, United Kingdom 1 year, China 5 years, Korea 7 years upon being granted conditional residency status (Williams & yu, 2006; Yu & Chen, 2018); dependence status where a qualitative finding revealed that men use deportation as a threat to the woman and her children to cage her and make her more vulnerable to domestic violence (Raj et al, 2019; Raj & Silverman, 2002; Tang & Wang, 2014); immigration flows restrictions (Carver, 2016); minimum available amount in a bank account to obtain a dependent status; in America, a K–1 or fiancée visa is issued with the condition that the couple marries within 90 days (US Dept. of Homeland Security, 2017); citizenship after 3 years of residence for those married to American citizens and 5 years for those married to Americans holding legal permanent residency (de Hart, 2017; Stamper Balistreri et al, 2017) and policies of probationary visa all renders women prone to domestic violence in their marital homes (Akyuz & Tursun, 2019; Anitha, 2019; Anitha et al, 2018; Kim, 2010, 2014; Kudo, 2017; Qureshi, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations